Analysis of Turkish cystic fibrosis chromosomes - Akarsubaşı, Alper Tunga. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1995., 1995)
Cystic fibrosis (CF results from mutations in the gene encoding the cystic fibrosis transmembrane regulator (CFTR), a protein that regulates chloride ion transport in exocrine gladns. Since the cloning of the gene, more than 375 disease-causing mutations have been identified. The major mutation in the gene is DF508, a deletion of three bp in exon 10 that removes a phenylalanine residue at position 508 and is found in 68 per cent of CF chromosomes worldwide. In this study, heteroduplex analysis was performed for detection of the mutations DF508 and 1677 delTA. The former was found in 15.5 per cent of CF chromosomes in Turkey. The latter was found in relatively high frequency (4.5 per cent) with respect to other mutations in our population. Further, DGGE analysis was used to detect mutations in exon 10, a mutation hot spot. A rare mutation, S466X, found in one patient, was the first case reported in the Turkish population. The DGGE migration pattern for the polymorphism 1540A/G was identified by DNA sequencing. It was confirmed with Hph I enzyme digestion and found with high frequency (37 per cent). Also, again by using Hph I digestion, the CF chromosomes were screened for an interesting mutation, 3849+10 kb C->T, which is associated with a mild type of disease. None of the patients were found to carry this mutation.
Keywords: Mutation (Biology); DNA damaged.